Havana storm - Cussler, Clive; Cussler, Dirk (New York : G.P. Putnam's Sons, 2014)
While investigating a toxic outbreak in the Caribbean Sea that may ultimately threaten the United States, Pitt unwittingly becomes involved in a post-Castro power struggle for the control of Cuba. Meanwhile, Pitt's children, marine engineer Dirk and oceanographer Summer, are on an investigation of their own, chasing an Aztec stone that may reveal the whereabouts of a vast historical Aztec treasure. The problem is, that stone was believed to have been destroyed on the battleship Maine in Havana Harbor in 1898.
Maps on lining papers.
Keywords: Pitt, Dirk -- (Fictitious character) -- Fiction; Marine biologists -- Fiction; Water -- Pollution -- Fiction; Cuba -- Fiction; Caribbean Area -- Fiction; Thrillers (Fiction); Action and adventure fiction